The impact of supply chain management and knowledge management practices on business performance among selected pharmaceutical manufactures in Bangladesh : a managerial perspective - Haque, Mahbubul (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
This era of globalization has generated unprecedented challenges for the companies in the market place, where the competition is now being waged between supply chains and not confined to only between companies any more. The conventional business models must, therefore, integrate an array of activities across the supply chains; this, however, calls for an effective knowledge transfer to the appropriate employees across the organizations. Dtie to its technological nature, the pharmaceutical industry is intimately involved in the adoption, generation and preservation of knowledge; thus for the strategic initiatives to bear fruits in this competitive business landscape, effective knowledge management across different entities of the supply chain is of utmost importance. The current research examines, from managerial perspective, the impact of supply chain management (SCM) and knowledge management (KM) practices on business performance among drug manufacturers in the pharmaceuticals industry of Bangladesh. In so doing, it explores the interrelationships among the above three constructs of the proposed model that incorporates two other mediating ones, namely, business competitiveness and customer satisfaction. For this purpose, a questionnaire containing fifty five statements, besides those of demographic and general information of the companies, is provided to the managers working in different pharmaceutical companies. In order to ensure the reliability of the measurement scales of the underlying constructs as well as the readability of the statements, a pilot study is performed. A total of three hundred and four managers have participated in this survey with a response rate of fifty eight percent. Structural equation modeling (SEM) is employed as the principal data analysis technique using software AMOS version 16.0. The findings of the study demonstrate that out of ten research hypotheses, five are validated with customer satisfaction fully mediating between the two antecedents, namely, SCM and KM practices and the two consequences, namely, business competitiveness and business performance. Five competing models are put forward and compared with the baseline model, the revised research framework. The study also performs two structural invariances and finds that although the managerial positions of the executives exert moderating influence on the baseline model, their boundary-spanning roles do not. The theoretical implications of the study call for adopting systems thinking theory and theory of constraints, where the current approach of cost minimization is to be supplanted by that of throughput maximization, with each entity considering its profitability being contingent upon that of the whole supply chain. The policy recommendations of the study vis-a-vis the industry relate to a host of issues: shrinking the current large supplier base, recognition of purchasing as a strategic weapon, considering the business operations from a holistic perspective and tailoring the IT infrastructure to the needs across the supply chain, the paramount importance of top management commitment and imparting of training, instituting benchmarking practices and rewarding the executives based on their know-how and for knowledge sharing in the performance appraisal process. The study concludes with a few limitations and suggestions for future research.